2013
DOI: 10.7448/ias.16.4.18972
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of HIV and prevention needs among men who have sex with men in Africa

Abstract: IntroductionMen who have sex with men (MSM) in Kenya are at high risk for HIV and may experience prejudiced treatment in health settings due to stigma. An on-line computer-facilitated MSM sensitivity programme was conducted to educate healthcare workers (HCWs) about the health issues and needs of MSM patients.MethodsSeventy-four HCWs from 49 ART-providing health facilities in the Kenyan Coast were recruited through purposive sampling to undergo a two-day MSM sensitivity training. We conducted eight focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 263 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Similar findings were reported in a study in Kenya, where fear of abnormal screening results (22.1%) and lack of financial support (11.4%) were the most common barriers to cervical cancer screening. 16 17 Another study in China showed that anxious feelings of diagnosis (47.6%) and lack of awareness of screening benefits (13.4%) were significant factors influencing cervical cancer screening. 18…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in a study in Kenya, where fear of abnormal screening results (22.1%) and lack of financial support (11.4%) were the most common barriers to cervical cancer screening. 16 17 Another study in China showed that anxious feelings of diagnosis (47.6%) and lack of awareness of screening benefits (13.4%) were significant factors influencing cervical cancer screening. 18…”
Section: Discussionmentioning
confidence: 99%